Some remarks on the textbook Język polski. Podręcznik dla klasy trzeciej by Barbara Rafałowska – a contribution to research on the publications of the Committee for Polish Children in the USSR (1943–1946) - Graczykowska, Tamara (Papers in Linguistics, 2025)
The Committee for Polish Children in the USSR (Kompoldiet) was established in Moscow following a political left-wing initiative and operated in the years 1943–1946. One of the most important issues in its activities was to provide Polish institutions in the USSR with school curricula, teaching materials, and textbooks. The aim of this article is to discuss Barbara Rafałowska’s Język polski. Podręcznik dla klasy trzeciej published by Kompoldiet in 1944 in terms of its ideological content and to analyse its linguistic design. The textbook, together with other publications of the Committee (textbooks for learning Polish, mathematics, geography, history, nature, or songbooks) will be part of a broader study – Zesłańcza „edukacja”. Podręczniki dla polskich dzieci opracowane przez Komitet ds. Dzieci Polskich w ZSRR w latach 1941–1946. Historia – ideologia – język. Examples discussed in the article, excerpted from Rafałowska’s textbook, both the linguistic ones and those related to ideological issues, show that the Kompoldiet publications are a valuable and rich source of material, and their scrutiny and compilation will lead to extending the knowledge on education in the USSR, especially during World War II, which is modest at the moment but very much needed.